Controller design for wind turbine systems - Lin, Chun Yew. (2009)
The project progress, research, and data of a wind turbine control system is summarized in this report, with main focuses on the process and development of the hardware and software components that is used to control the output electrical power supply of a wind turbine via the control of variable pitch angle.